A Defective Pentose Phosphate Pathway Reduces Inflammatory Macrophage Responses during Hypercholesterolemia - Baardman, Jeroen; Verberk, Sanne G.S.; Prange, Koen H.M.; van Weeghel, Michel; van der Velden, Saskia; Ryan, Dylan G.; Wüst, Rob C.I.; Neele, Annette E.; Speijer, Dave; Denis, Simone W.; Witte, Maarten E.; Houtkooper, Riekelt H.; et al. (Cell reports (Cambridge), 2018)
Metabolic reprogramming has emerged as a crucial regulator of immune cell activation, but how systemic metabolism influences immune cell metabolism and function remains to be investigated. To investigate the effect of dyslipidemia on immune cell metabolism, we performed in-depth transcriptional, metabolic, and functional characterization of macrophages isolated from hypercholesterolemic mice. Systemic metabolic changes in such mice alter cellular macrophage metabolism and attenuate inflammatory macrophage responses. In addition to diminished maximal mitochondrial respiration, hypercholesterolemia reduces the LPS-mediated induction of the pentose phosphate pathway (PPP) and the Nrf2-mediated oxidative stress response. Our observation that suppression of the PPP diminishes LPS-induced cytokine secretion supports the notion that this pathway contributes to inflammatory macrophage responses. Overall, this study reveals that systemic and cellular metabolism are strongly interconnected, together dictating macrophage phenotype and function. [Display omitted] •Systemic metabolism affects immune cell metabolism•Hypercholesterolemia suppresses the PPP and Nrf2 pathway in macrophages•PPP inhibition and hypercholesterolemia deactivate inflammatory macrophage responses•The Nrf2 pathway regulates the PPP in an LXR-independent manner The link between systemic and cellular metabolism is a neglected aspect in immunometabolism. Baardman et al. show that hypercholesterolemia alters macrophage metabolism and phenotype. The suppressed pentose phosphate pathway (PPP) in those “foam cell” macrophages attenuates inflammatory responses, signifying that systemic and cellular metabolism together regulate macrophage function.